Pendampingan Pembuatan Nomor Induk Berusaha (NIB) Bagi Pelaku UMKM di Kabupaten Pekalongan - Khuly Shofiana; Tsania Umairo; Muhammad Sultan Mubarok (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
This community service aims to increase awareness of business actors about the importance of having a Business Identification Number (NIB) and also aims to support efforts to orderly administer government regulations. With this community service activity, it is hoped that it can help business actors in obtaining a Business Identification Number (NIB) without excessive costs or without additional costs. This study uses a qualitative approach, with data collection techniques through direct counseling to MSME actors around UIN K.H. Abdurrahman Wahid Pekalongan. The results of this study concluded that the creation of a Business Identification Number (NIB) was intended so that MSMEs around UIN K.H. Abdurrahman Wahid Pekalongan have business legality. The creation of a Business Identification Number (NIB) was carried out independently by researchers using the Online Single Submission (OSS) system. Then the results of the submission of the Business Identification Number (NIB) were printed and given directly to the relevant MSME actors. The Business Identification Number (NIB) is beneficial for MSMEs, because their businesses will receive legal protection as well as business development opportunities, both through training and technical guidance, as well as through financial access, such as the possibility of obtaining capital loans from financial institutions.